Omega-3 supplementation and cardiometabolic risk factors in obese/overweight children and adolescents: a GRADE assessed systematic review and meta-analysis - Vali Musazadeh; Mahsa Mahmoudinezhad; Pedram Pam; Sanaz Brazandeh; Fatemeh Faramarzi; Yousef Mohammadpour; Amir Hossein Faghfouri; Shahsanam Gheibi (Nutrition & Metabolism)
Abstract Background Omega-3 polyunsaturated fatty acids (ɷ3 PUFA), have been proposed as a supplement to improve cardiometabolic risk factors in obese/overweight children and adolescents. However, findings evidence remains inconsistent. This meta-analysis aimed to assess the effects of ɷ-3 PUFA supplementation on cardiometabolic risk factors in obese/overweight children and adolescents. Methods A systematic review of PubMed, Embase, Scopus, Web of Science, Cochrane Library, and Google Scholar up to January 2024 was searched. Data were pooled using a random-effects model to calculate Weighted mean differences (WMDs) and 95% Confidence intervals (CIs). Results Nine studies with 595 participants were included. The meta-analysis revealed that ɷ-3 PUFA supplementation significantly reduced Body mass index (BMI) (WMD = -0.39 kg/m²; 95% CI: -0.72, -0.05, I2 = 0.0%, P = 0.497), triglyceride (TG) (WMD = -23.54 mg/dl, 95% CI: -42.90, -4.18, I2 = 89.2%, P < 0.001), and Homeostatic model assessment for insulin resistance (HOMA-IR) (WMD = -0.38, 95% CI: -0.67, -0.10, I2 = 53.6%, P = 0.071). However, ɷ-3 PUFA supplementation did not significantly affect weight, BMI-Z score, Fasting blood sugar (FBS), insulin, Total cholesterol (TC), Low-density lipoprotein- cholesterol (LDL-C), and High-density lipoprotein-cholesterol (HDL-C). Moreover, subgroup analysis elucidated that ɷ-3 supplementation has more pronounced effects in higher doses (> 1500 mg/ day) in term of BMI, LDL-c, TG. The quality of the included studies was assessed using the Cochrane risk-of-bias tool (RoB 2), which identified eight studies as having a high risk of bias. Additionally, the GRADE assessment indicated a high quality of evidence for BMI, HOMA-IR, TG and moderate quality for weight, FBS, TC, LDL-c, and HDL-c values. Conclusions The current meta-analysis revealed that ɷ3 PUFA supplementation beneficial effect on BMI, HOMA-IR, and TG levels. No favorable effect of ɷ3 PUFA supplementation on weight, BMI z-score, TC, LDL-C, HDL-C, FBS and insulin was observed.